2020
DOI: 10.1128/mbio.01333-20
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing Nudivirus Assembly and Egress

Abstract: Enveloped viruses hijack cellular membranes in order to provide the necessary material for virion assembly. In particular, viruses that replicate and assemble inside the nucleus have developed special approaches to modify the nuclear landscape for their advantage. We used electron microscopy to investigate cellular changes occurring during nudivirus infection and we characterized a unique mechanism for assembly, packaging, and transport of new virions across the nuclear membrane and through the cytoplasm. Our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…The major contribution of nudiviruses to endogenization may be explained by their wide host range in arthropods [45]. Their nuclear replication constitutes another plausible explanatory factor [46], since it may facilitate contact with host DNA. In addition, their tropism for gonads may favor the endogenization in germinal cells [47].…”
Section: Dsdna Viruses Are More Frequently Involved In Endogenization...mentioning
confidence: 99%
“…The major contribution of nudiviruses to endogenization may be explained by their wide host range in arthropods [45]. Their nuclear replication constitutes another plausible explanatory factor [46], since it may facilitate contact with host DNA. In addition, their tropism for gonads may favor the endogenization in germinal cells [47].…”
Section: Dsdna Viruses Are More Frequently Involved In Endogenization...mentioning
confidence: 99%
“…Valuable tool in understanding hair biology. 130,135 Correlative light and electron microscopy (CLEM) Specific proteins localized at an ultrastructure level using nano gold markers.…”
Section: 133mentioning
confidence: 99%
“…The development of electron tomography and volume microscopy has aided in the 3D visualization of the precise geometry of complex macromolecular, subcellular or cellular structures including interaction of keratins and desmosomes. 25,[130][131][132] CLEM of high-pressure frozen and freezesubstituted samples, rather than a conventionally processed sample, can be ideal for simultaneously preserving the ultrastructural and antigenic epitopes; and dark-field scanning transmission electron microscopy (DF-STEM) then enables visualization of immunogold markers at high-resolution without the need for any post-staining or silver enhancement procedures. 71 While advancements in electron tomography have enabled the 3D visualization of macromolecular process, a limited sampling volume limits the investigation of features that span more than a few…”
Section: Overvie W Of Tem Technique S and Con Clus Ionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the occurrence of release, the host cell membrane can be hijacked or fused with the viral membrane in the enveloped virus. 7,8 ESCRT pathway usually participates in RNA viruses' intracellular replication, such as human immunodeficiency virus (HIV), 9 and bluetongue virus (BTV), 10 and also in a certain kind of DNA virus' replications including herpes simplex virus (HSV), 11,12 hepatitis B virus (HBV), 13 and Epstein-Barr virus (EBV). 14 Emerging studies have revealed that multiply nonenveloped viruses may also hijack cell membranes, allowing them to lurk in the membrane to facilitate immune escape or avoid immune neutralization and clearance.…”
Section: Introductionmentioning
confidence: 99%